2015
DOI: 10.3892/mco.2015.651
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cancer stem cell marker CD133 expression in esophageal carcinoma: A meta-analysis

Abstract: Abstract. CD133 has been identified as a putative neoplastic stem cell marker in esophageal carcinoma. However, the prognostic value of CD133 overexpression in patients with esophageal carcinoma remains controversial. A meta-analysis of previous studies was performed, in order to assess the association of CD133 overexpression with the clinicopathological characteristics of esophageal carcinoma patients. A total of 7 studies, including 538 patients, were subjected to the final analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Two meta-analyses have shown that higher CD133 levels are significantly associated with lymph node metastasis, clinical stage, and histopathological grade in colorectal cancer and esophageal carcinoma patients [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Two meta-analyses have shown that higher CD133 levels are significantly associated with lymph node metastasis, clinical stage, and histopathological grade in colorectal cancer and esophageal carcinoma patients [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, PROM1 upregulation has been reported in ovarian cancer [88,89] and targeting this gene retards ovarian cancer development in an in vivo model [90]. Furthermore, PROM1 has been identified as a stem cell marker in esophageal and breast cancers [5,56]. Next, we observed that PROM2 upregulation was associated with poor OS in lung cancer; however, owing to contradictory results, its role in breast cancer was not clear and the receptor status of breast cancer cells also had some Fig.…”
Section: Discussionmentioning
confidence: 76%
“…These results regarding PROM1 and PROM2 expression are also supported by previous studies. For example, PROM1 overexpression has been shown in esophageal and ovarian cancers [56,57]. Moreover, PROM1+ ovarian CSCs are highly tumorigenic, chemoresistant, and metastatic and they promote the adhesion capabilities of the ovarian cancer metastatic niche [57].…”
Section: Prominin Mrna Expression Analysismentioning
confidence: 99%
“…In particular, some studies have proposed CD44 as a CSC marker in ESCC [ 29 , 31 ]. Functional characteristics were also found for CD133 [ 32 , 33 , 34 ], CD271(p75NTR) [ 35 , 36 , 37 ], LgR5 [ 38 , 39 , 40 ], CD90 [ 41 , 42 ], ALDH1 [ 43 , 44 , 45 ], ABCG2 [ 33 , 46 , 47 ], ICAM-1[ 48 ] and ITGA7 [ 49 ]. Besides, CD44 and CD133 can be used in combination with CD24 (CD44 + /CD24 − ) [ 50 ], CD133 (CD44 + /CD133 + )[ 51 ] and CXCR4 (CD133 + /CXCR4 + ) [ 52 ] to identify esophageal CSCs ( Table 1 ).…”
Section: Isolation Of Esophageal Cancer Stem Cellsmentioning
confidence: 99%